WAYS TO IMPROVE THE MORTGAGE LENDING PRACTICE IN COMMERCIAL BANKS - Otabek Olimovich Muslimov; Nuriddin Sayfulloyevich Kayumov (European Science Publishing, 2024)
Mortgage loan is one of the most important tasks of commercial banks, serves as the basis of financial services and helps to buy housing. This article examines the main strategies aimed at improving mortgage lending practices in commercial banks. Based on industry knowledge and best practices, it outlines practical steps to improve operational efficiency, manage risk, customer engagement and compliance. By adopting an integrated approach to mortgage lending, commercial banks can optimize their processes, reduce risks and better meet the changing needs of borrowers and stakeholders.
Keywords: Mortgage lending, commercial banking, practice improvement, strategic imperative, digital transformation, risk management, customer engagement, regulatory compliance, operational efficiency, financial inclusion.